FUNDAMENTAL STUDY ON METAL DUSTING PREVENTION OF AISI 316 STAINLESS STEELS BY USING COPPER COATING - Suryanto, -; Ani, Mohd Hanafi; Yaacob, Iskandar Idris; Haider I., Farag (2018)
Metal dusting corrosion is high-temperature degradation of metals and alloys into dust-like fine particles. It is often encountered in petrochemical industry, where metals and alloys extensively exposed to carbon-containing gases at high temperature. It is a costly issue in the industry; millions of dollars have been invested annually in the fields of monitoring, controlling and prevention of metal dusting corrosion to avoid potential dangers in the environments that are considered by explosive and/or poisonous gases under high pressure and temperature conditions. Metal dusting initiates as a result of unwanted carbon formation on the surface of metallic engineering installations. At high temperature, solid carbon diffuses into the metal/alloy matrix to form a carburised layer on the surface. Under certain conditions, this carburised region may become unstable and decompose into carbon and metal/alloy particles, as well as other corrosion products. Such as metal particles may further catalyse the carbon deposition and the process are hence accelerated. Thus, the primary aim of this study is to prevent carbon diffusion into metal in order to mitigate the metal dusting corrosion by using an electroplating copper coating on 304L and 316L stainless steels. Therefore, coated and non-coated 304L and 316L samples were exposed to metal dusting environment in a 10% to 50% CH4/H2 gas mixture, at temperature range of 600˚C - 800˚C, and a pressure of 1 atm, leading to carbon activities from 0.203 to 3.289 for 100hours. Optical microscopy (OM) results revealed that the electroplating copper coating mitigates carbon from diffuse into metal, so no carburization zone was formed, compared with non-coated samples which displayed clear carburization were formed for both 304L and 316L stainless steel at temperatures more than 600˚C and gas mixture 20% CH4/H2 and above where carbon activity approach to 1. Weight gain test showed non-significant weight gain on coated samples compared to non-coated samples. These values of weight gain increase with increase the temperature or/and CH4/H2 gas mixture. This result also confirmed by X-Ray Diffraction (XRD) and scanning electron microscope (SEM) coupled with energy dispersive x-ray (EDX) which showed no carbides formed on the surfaces of coated samples. M7C3 carbides were formed on the surface of non-coated samples as a result of diffuse carbon in the metal and react with elements. in this experiments, electroplating copper coated samples showed negligible carbon deposition on the surface and no carbon diffusion into metal. Thus, electroplating copper coating is solution to mitigate metal dusting corrosion